PERANCANGAN KORIDOR JALAN DIPONEGORO PONTIANAK, KALIMANTAN BARAT - Ikhtiari, Anang Ridha; Aufa, Naimatul (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Diponegoro Street is a festival road and has a corridor, the corridor has no space to support festival activities or other social activities. The design of the Diponegoro Street Corridor is a public space, has a function as social space, and Pontianak cultural space (Malay, Dayak, and Chinese). The goal is achieved by applying the concept of